2016
DOI: 10.1002/ptr.5558
|View full text |Cite
|
Sign up to set email alerts
|

New Findings on the Effects of Tannic Acid: Inhibition of L‐Type Calcium Channels, Calcium Transient and Contractility in Rat Ventricular Myocytes

Abstract: Tannic acid (TA) is a group of water-soluble polyphenolic compounds that occur mainly in plant-derived feeds, food grains and fruits. Many studies have explored its biomedical properties, such as anticancer, antibacterial, antimutagenic, antioxidant, antidiabetic, antiinflammatory and antihypertensive activities. However, the effects of TA on the L-type Ca(2+) current (ICa-L) of cardiomyocytes remain undefined. The present study examined the effects of TA on ICa-L using the whole-cell patch-clamp technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Tannic acid was shown to inhibit CaCCs formed by TMEM16A and B (Cruz-Rangel et al, 2015; Namkung et al, 2010, 2011) and TMEM16F (Szteyn et al, 2012), which is consistent with an antidiarrhoeic activity of tannin-containing extracts reported earlier (Galvez et al, 1991). Tannic acid also blocks L-type Ca-channels (Zhu et al, 2016) and the maxi-anion channel (Woll et al, 1987). The latter is known to be swelling-activated (Okada et al, 2018(Okada et al, , 2019Sabirov & Merzlyak, 2012;Sabirov et al, 2016), although it operates mostly when cells are metabolically deprived, whereas VSOR is the major contributor to the swellingactivated plasmalemmal conductance at normal intracellular ATP levels.…”
Section: Introductionsupporting
confidence: 54%
“…Tannic acid was shown to inhibit CaCCs formed by TMEM16A and B (Cruz-Rangel et al, 2015; Namkung et al, 2010, 2011) and TMEM16F (Szteyn et al, 2012), which is consistent with an antidiarrhoeic activity of tannin-containing extracts reported earlier (Galvez et al, 1991). Tannic acid also blocks L-type Ca-channels (Zhu et al, 2016) and the maxi-anion channel (Woll et al, 1987). The latter is known to be swelling-activated (Okada et al, 2018(Okada et al, , 2019Sabirov & Merzlyak, 2012;Sabirov et al, 2016), although it operates mostly when cells are metabolically deprived, whereas VSOR is the major contributor to the swellingactivated plasmalemmal conductance at normal intracellular ATP levels.…”
Section: Introductionsupporting
confidence: 54%
“…The biochemical blood profile was only slightly affected by TA level. Feeding diets with 2% of TA considerably reduced the activity of CK, a cardiac marker enzyme, which was in agreement with previous findings of cardioprotective effects of TA and other polyphenols [ 4 , 26 , 27 ]. It has recently been suggested that TA maintains the integrity of the cardiac cell membrane and prevents the leakage of CK and other cytosolic enzymes into the bloodstream [ 4 ], which seems to be confirmed by the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…TA may exert its cardioprotective effect by reduction of Bax/Bcl-2 ratio, expression of c-fos and c-jun, inhibition of NF-κB activation, as well as due to antioxidative and antiinflammatory properties [ 4 ]. Cellular mechanism of TA activity also include inhibition of L-type Ca 2+ channels in cardiomyocytes [ 27 ]. The effect of TA on blood phosphorus level is difficult to explain and it is not clear why feeding diets with 0.25% and 2% of TA elevated its concentration compared to rats on the 1% TA diets.…”
Section: Discussionmentioning
confidence: 99%
“…Such calcium channels cause divalent cation entry and induce iron‐overload which is consequently blocked by channel blockers. Moreover it has been observed that TA could inhibit L‐type calcium channels . Thus it can be envisaged that TA might modulate DMT‐1 and block L‐type calcium channels and reverse iron overload in the body.…”
Section: Discussionmentioning
confidence: 99%